2012
DOI: 10.6061/clinics/2012(01)08
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic responses and upper airway morbidity following tracheal intubation in patients with hypertension: Conventional laryngoscopy versus an intubating laryngeal mask airway

Abstract: OBJECTIVES:We compared hemodynamic responses and upper airway morbidity following tracheal intubation via conventional laryngoscopy or intubating laryngeal mask airway in hypertensive patients.METHODS:Forty-two hypertensive patients received a conventional laryngoscopy or were intubated with a intubating laryngeal mask airway. Anesthesia was induced with propofol, fentanyl, and cis-atracurium. Measurements of systolic and diastolic blood pressures, heart rate, rate pressure product, and ST segment changes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
2
17
1
1
Order By: Relevance
“…However, it is in contrast to the result of Lee et al (9). Airways suctioning is an invasive procedure and can result in increased blood pressure as well as heart rate through sympathetic system stimulation mechanisms (29). It can be noted that in similar studies, the selected subjects had various modes of ventilation and the patients did not have similar PEEP while in the present study, all the subjects were under SIMV mode and their PEEP was fixed as 5 cm H 2 O in ventilator.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is in contrast to the result of Lee et al (9). Airways suctioning is an invasive procedure and can result in increased blood pressure as well as heart rate through sympathetic system stimulation mechanisms (29). It can be noted that in similar studies, the selected subjects had various modes of ventilation and the patients did not have similar PEEP while in the present study, all the subjects were under SIMV mode and their PEEP was fixed as 5 cm H 2 O in ventilator.…”
Section: Discussionmentioning
confidence: 99%
“…[18] also found significant increase in heart rate and blood pressure in both DLS and ILMA groups after intubation, but quantity of these changes was similar in both groups. In contrast to above studies Sener et al [19] found ILMA aided intubation to have higher sympathetic response when compared to DLS in 42 patients with controlled hypertension. They found intubation with DLS was accompanied by a smaller increase in blood pressure and rate pressure product at 1 and 2 min following intubation than with the ILMA method.…”
Section: Resultsmentioning
confidence: 77%
“…Laringoskopi dan intubasi ini selain dapat menyebabkan trauma, juga dapat menimbulkan gejolak kardiovaskuler berupa peningkatan tekanan darah, peningkatan laju jantung dan disritmia. 2,3 Hal ini disebabkan oleh respon aktivitas simpatis dan pelepasan katekolamin akibat rangsangan pada daerah laring, trakea, karina dan bronkus. 4,5,6 Pada orang sehat respon ini sebagian besar dapat ditoleransi, tetapi lidokain, fentanyl, remifentanil, alfentanil, penyekat beta, nifedipin, klonidin dan diltiazem.…”
Section: Pendahuluanunclassified